2023
DOI: 10.1037/aca0000546
|View full text |Cite
|
Sign up to set email alerts
|

Slow looking at still art: The effect of manipulating audio context and image category on mood and engagement during an online slow looking exercise.

Abstract: In the past two decades, "slow looking" has emerged as an engaging art-viewing approach used by museums around the world as part of their in-person and online programming, but there has been little empirical inquiry into the precise effects of the practice. This study represents the first such attempt, exploring reported impacts of slow looking within an online context. Specifically, the study examined the effects of two factors -audio context (control, meditation, historical) and image category (photography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In all conditions, people felt more pleasant and relaxed following their slow looking experience, and the art historical condition had higher cultural engagement and overall aesthetic experience scores. These findings suggest slow looking as a practice has beneficial impacts and that the nature of focus during slow looking may have differential impacts on viewing outcomes (Igdalova & Chamberlain, 2022). This study, although an important initial examination of slow looking practices, did not include a non-slow looking control condition and also had all participants engage in a brief mediation prior to engaging in slow looking, which limits our understanding of how slow looking may be more beneficial than more typical art-viewing behaviors.…”
Section: Immersive Art Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…In all conditions, people felt more pleasant and relaxed following their slow looking experience, and the art historical condition had higher cultural engagement and overall aesthetic experience scores. These findings suggest slow looking as a practice has beneficial impacts and that the nature of focus during slow looking may have differential impacts on viewing outcomes (Igdalova & Chamberlain, 2022). This study, although an important initial examination of slow looking practices, did not include a non-slow looking control condition and also had all participants engage in a brief mediation prior to engaging in slow looking, which limits our understanding of how slow looking may be more beneficial than more typical art-viewing behaviors.…”
Section: Immersive Art Engagementmentioning
confidence: 99%
“…Surprisingly, only one study has experimentally examined the impacts of slow looking through varying the information available to participants during the slow looking period (Igdalova & Chamberlain, 2022). In this study, people engaged in three 3-minute online slow looking exercises and were randomly assigned to listen to a control text not providing any specific instructions and telling people to view the work as they wished, a text describing and encouraging mindfulness mediation, or a text providing art historical information relevant to the artworks.…”
Section: Immersive Art Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in terms of intervention design, the artwork used in the study could be expanded to apply the protocol with the gallery’s expansive range of Southeast Asian artworks. Comparative evaluation between art works and modalities could be explored further as research has suggested that specific elements within different types of artworks may be more suited for slow looking ( 78 , 79 ). In addition, a multi-session Slow Art Plus could be further developed and tested using a longitudinal research design to investigate the intervention’s effectiveness across a longer period as suggested by some participants who expressed a desire for more sessions to explore various art and meditation techniques and to build stronger connections with other Slow Art Plus participants.…”
Section: Discussionmentioning
confidence: 99%
“…In the visual art domain, there is evidence from Zabelina et al (2020) that mindfulness-based practices may not only result in a deeper art viewing experience, but also may go along with more creative and expressive personal art. Also, Igdalova and Chamberlain (2023) found that “slow looking” in the context of art-viewing contributed to more pleasant experiences and a greater feeling of calmness.…”
mentioning
confidence: 95%